Comparison of SaCoVLM™ video laryngeal mask-guided intubation and i-gel combined with flexible bronchoscopy-guided intubation in airway management during general anesthesia: a non-inferiority study - Chun-ling Yan; Yi-qi-yuan Zhang; Ying Chen; Zong-yang Qv; Ming-zhang Zuo (BMC Anesthesiology, 2022)
Abstract Background When a difficult airway is unanticipatedly encountered and the initial laryngoscopic intubation fails, a supraglottic airway device (SAD) may be placed to aid ventilation and oxygenation, and act as a conduit for intubation. SaCoVLM™, as new SAD, can offer a direct vision to guide intubation. However, no study has evaluated the performance of SaCoVLM™ video laryngeal mask (VLM) intubation and i-gel combined with flexible bronchoscopy (FB)-guided intubation in airway management during general anesthesia. Methods A total of 120 adult patients were randomly allocated into the SaCoVLM™ group (Group S) and i-gel group (Group I). After induction of general anesthesia, guided tracheal intubation under direct vision of the SaCoVLM™ was conducted in Group S, while Group I received FB-guided tracheal intubation using the i-gel. The success rate of SAD placement, first-pass success rate of guided tracheal tube placement, and total success rate in both groups were recorded. The time for SAD placement, time for guided tracheal intubation, total intubation time (time for SAD placement and intubation), glottic exposure grading and postoperative intubation complications (i.e., dysphagia, hoarseness, pharyngalgia, etc.) of both groups were also compared. Results The first-time success rate of SAD placement was 98% in two groups. The first-pass success rate of guided endotracheal intubation was 92% in Group S and 93% in Group I (P = 0.74 > 0.05). The total intubation time was 30.8(± 9.7) s and 57.4(± 16.6) s (95% CI = -31.5 to -21.7) in Group S and Group I, respectively (P < 0.01). The total complication rate was 8% in Group S and 22% in Group I (P < 0.05). The laryngeal inlet could be observed in the S group through the visual system of SaCoVLM™. No dysphagia or hoarseness was reported. Conclusion SaCoVLM™ can reveal the position of laryngeal inlet, thus providing direct vision for tracheal intubation. SaCoVLM™ -guided intubation is faster, and does not rely on FB, compared to i-gel combined with FB-guided intubation. Besides, SaCoVLM™ has a lower post-intubation complication rate. Trial registration Chinese Clinical Trials Registry (ChiCTR2100043443); Date of registration: 18/02/2021.